FINANCIAL LITERACY, KONTROL DIRI, GAYA HIDUP, MATERIALISTIS TERHADAP PERSONAL FINANCIAL MANAJEMEN - Sari, Dina Fahma; Naimatul Inayah Wulandari (Juremi: Jurnal Riset Ekonomi, 2023)
The research objective was to determine the effect of Financial Literacy, self-control, lifestyle and materialism on personal financial management. The research approach uses a quantitative research approach by distributing questionnaires at several private campuses in the City and District of Pasuruan with a total sample of 119 students. Sampling using purposive sample technique. Data analysis techniques using SPSS. The research results show that Financial Literacy has a significant effect on Personal Financial Management. Self-Control has a significant effect on Personal Financial Management. Lifestyle has no significant effect on Personal Financial Management. Materialistic has no significant effect on Personal Financial Management.